DC Electrical Ageing of XLPE under Hydrostatic Pressure - Fadila Benlizidia Lalam; Faouzi Djemmal (Advances in Materials Science and Engineering)
The experimental electrical ageing, of cross-linked polyethylene films 100 μm thick, was investigated under high hydrostatic pressure of 300 bar and at atmospheric pressure. The tests are conducted on direct current (dc) for up to 1000 h ageing and at temperature of 70°C. The use of the Weibull statistic, with the estimation of confidence bounds at 90%, has shown that the hydrostatic pressure has a real effect on the lifetime. These lifetime data are qualitatively analyzed with the inverse power model. It was found that thermally activated process is able to describe the pressure effect on the electrical ageing of XLPE.